Prevalence of Hypertension in Area I Cienfuegos Municipality. Second Measurement of CARMEN Initiative - Hilda María Delgado Acosta; Karelis Lastre Navarro; María Lina Valdés Gómez; Mikhail Benet Rodríguez; Alain Francisco Morejón Giraldoni; Juan Rafael Zerquera Rodríguez (Revista Finlay)
Background: the prevalence of hypertension has increased, associated to inadequate alimentary patterns, decrease of physical activity, and other behaviour patterns related to toxic habits. Objective: characterizing the prevalence of hypertension in the Area I Cienfuegos in 2010 - 2011. Methods: a descriptive and cross-section study was conducted. The sampling units were: districts, areas and sections that contained the houses, were the individuals were selected; the sample consisted on 373 people, their blood pressure was taken and an opinion poll was applied, the variables were: age, sex, personal record of hypertension and diabetes mellitus, tobacco addiction, type of physical activity, weight, size, abdominal circumference. Results: prevalence of hypertension was a 33.8 %, with predominance of the masculine sex, the 65.0 % of the hypertensive knew their condition and a 35.0 % was hypertensive and did not know it. Only the 23.8 % of the total of them were controlled, and the 44.1 % of them were under treatment. The prevalence of hypertension among smokers was 32.7 %. The 55% were diabetics, the 46.5 % were obese and the 50 % had an altered measurement of the abdominal waist. Conclusions: it was detected a hidden prevalence of hypertension and lack of control in patients under treatment with predominance of the masculine sex, among the studied risk factors, the diabetics and the obese presented a prevalence of hypertension two times bigger than the ones that did not have these risk factors.